2004
DOI: 10.1196/annals.1293.011
|View full text |Cite
|
Sign up to set email alerts
|

Biological Significance of the Defense Mechanisms against Oxidative Damage in Nucleic Acids Caused by Reactive Oxygen Species: From Mitochondria to Nuclei

Abstract: In mammalian cells, more than one genome in a single cell has to be maintained throughout the entire life of the cell, namely, one in the nucleus and the other in the mitochondria. The genomes and their precursor nucleotides are highly exposed to reactive oxygen species, which are inevitably generated as a result of the respiratory function in mitochondria. To counteract such oxidative damage in nucleic acids, cells are equipped with several defense mechanisms. Modified nucleotides in the nucleotide pools are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…3,4 It has been established that oxidative DNA damage, such as 8-oxoguanine (8-oxoG), accumulates both in nuclear and mitochondrial genomes during aging, 5,6 and such accumulation is likely to increase dramatically in patients with tumors 7 or various neurodegenerative diseases, such as Parkinson's disease (PD), 8,9 Alzheimer's disease (AD) 10 or amyotrophic lateral sclerosis. 11 We have shown that a significant increase of 8-oxoG accumulated in the cytoplasm or mitochondria with a coincidentally elevated expression of MTH1 in the substantia nigral neurons of PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 It has been established that oxidative DNA damage, such as 8-oxoguanine (8-oxoG), accumulates both in nuclear and mitochondrial genomes during aging, 5,6 and such accumulation is likely to increase dramatically in patients with tumors 7 or various neurodegenerative diseases, such as Parkinson's disease (PD), 8,9 Alzheimer's disease (AD) 10 or amyotrophic lateral sclerosis. 11 We have shown that a significant increase of 8-oxoG accumulated in the cytoplasm or mitochondria with a coincidentally elevated expression of MTH1 in the substantia nigral neurons of PD patients.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that the hMTH1 protein was correctly transported into the chloroplasts and mitochondria of the chl-hMTH1 and mit-hMTH1 plants, respectively. It has been reported that the hMTH1 gene produces various types of hMTH1 polypeptides by alternative splicing events (Nakabeppu et al 2004). hMTH1d, whose cDNA was used for this study, is the major form among the splicing variants and mostly localized in the cytosol with approximately 5% in the mitochondrial matrix and a lesser amount in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Mammalian cells also contain multiple enzymes homologous to E. coli MutT, such as MutT homologs 1, 2 and 3 (MTH1, MTH2 and MTH3) and NUDT5 (Mo et al 1992, Sakumi et al 1993, Cai et al 2003, Ishibashi et al 2005, Takagi et al 2012. Human MTH1 (hMTH1) has both 8-oxo-(d)GTP and 2-OH-(d)ATP pyrophosphohydrolase activities and is localized not only to the cytosol, but also to the nucleus and mitochondria, which possesses its own genome DNA (Nakabeppu et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Minor modifications of the nucleic acid bases are repaired through base excision repair involving DNA glycosylase and AP endonuclease, which are located in nuclei and mitochondria. The progression of AD is associated with the diminished expression of these DNA repair enzymes (Nakabeppu et al, 2004). The accumulation of the oxidatively damaged nucleic acids and proteins likely exceeds the limit of cellular repair and detoxification mechanisms and leads to the onset or progression of diabetic and neurological pathologies.…”
Section: The Effect Of Oxidative Stressmentioning
confidence: 99%